PARADIGMA PORNOGRAFI DALAM ASPEK HUKUM - Asili Asili (An Nisa'a, 2012)
Today gender has become a big issue coloring various aspects  of life, in the field of epistemology, science, law, economy, politics, culture and even in the religious field.Indonesia, with its patriarchic culture, consciously or not, has constructed a gender difference which tends to be advantageous for men and placed women in a subordinate position. This article describes more about how law inIndonesiasticks up for women.